352 Grey and White Matters – Designing and Implementing an Acute Stroke Program in a level 3 Hospital. (16th September 2019) - Daly, Bart; Liston, Richard; Griffin, Susan
Abstract: Background: Following the publication of the National Stroke Audit in 2015 with below the national average rates of thrombolysis – 3.3% versus 11% - there has been a number of initiatives launched to improve stroke care in this hospital. In 2018 we enrolled in the National Quality Improvement Project for the care of Patients with Acute Ischaemic Stroke run by the RCSI. A stroke steering committee was established consisting of a multi-disciplinary group encompassing all areas of acute stroke care. Methods: Acute stroke care practice and factors causing sub-optimal management were examined by the committee and compared with national standards. A '3 jobs' proforma for management and communication of Fast positive cases was designed to address the difficulties identified in stroke care and tailored to the resources available in this hospital. These simplified and standardised roles for all staff members involved, many of whom were unfamiliar with the practical delivery of thrombolysis and thrombectomy. Educational sessions were initiated for all those involved in acute stroke management. The acute stroke program was implemented as a 6 month pilot before official launch in April 2019 with necessary changes assessed weekly by the stroke committee. Stroke data is continually audited with the National Stroke Register. Key Performance Indicators (KPI's) in the pilot were thrombolysis/thrombectomy rates and door to needle time. Results: There were 164 patients admitted to the stroke unit in 2018. In 2018 prior to this initiative, the hospital had a 3% thrombolysis rate in 2018 and a 1% thrombectomy rate. Amongst FAST positive patients during the pilot period, 10/68 patients were thombolysed (15%) and 6/68 thrombectomies (9%). Average door to needle time for patients was 96 minutes. Conclusion: The redesigning of the acute stroke care program has led to significant improvements in the identified KPI's although door to needle times remain below the national target of 30 minutes.